THE EFFECTIVENESS OF MENTORING AND COACHING IN THE CAREER DEVELOPMENT OF NURSES INTO THE TERTIARY HEALTHCARE (Journal of Medical & Health Sciences Review, 2025)
Mentoring and coaching are fundamental strategies in the career development of nurses in tertiary healthcare settings fostering professional growth, clinical competency and job satisfaction. This study explores the effectiveness of mentorship programs identifying key challenges and areas for improvement. The findings indicate that while most nursing mentors express confidence in their ability to guide students, inconsistencies in structured mentorship programs and feedback mechanisms hinder their overall effectiveness. Many mentors demonstrate motivation to engage in student development yet a lack of formal training and standardized mentoring approaches results in varied mentorship quality. The research highlights a significant gap in structured goal-setting with some mentors failing to provide clear learning objectives or engage in progress discussions limiting student competency development. Additionally, while some mentors provide constructive feedback, others struggle with balancing positive reinforcement and critical evaluations which can negatively impact student motivation and learning outcomes. The study also emphasizes the absence of formal mentorship programs in many healthcare institutions leading to missed opportunities for skill transfer, leadership development and professional networking among nurses. To address these challenges, the study suggests implementing structured mentorship programs providing targeted mentor training and incorporating regular feedback and reflection practices into nursing education. By improving mentorship consistency and effectiveness healthcare institutions can enhance job satisfaction, strengthen clinical competency and cultivate a well-prepared nursing workforce capable of meeting the demands of modern healthcare. This research underscores the critical need for institutional support in establishing sustainable mentorship programs that not only benefit nursing professionals but also improve overall patient care and healthcare system efficiency.